gestión del trabajador social frente al impacto ambiental en urseza 3 sector 4 de la parroquia puerto bolívar, machala, 2023. - Carrion Torres, Lizbeth Yomaira; Diaz Pineda, Marlen Fernanda (Machala, 2025)
This analysis deals with the environmental problems in the Urseza 3-sector 4 neighborhood of the parish of Puerto Bolivar, Machala, focusing on the role of the social worker in the management of environmental impact. The environmental conditions of the area, the community's opinions about pollution and the tactics implemented to mitigate its adverse impacts are analyzed. Using a participatory method, the study aims to understand the connection between environmental management and the community, highlighting the relevance of environmental education and cooperation between social and governmental entities. To achieve this, qualitative techniques were used, including interviews with residents and community leaders, direct observations and document review. The study is based on ecological theories and community intervention models, which facilitate the understanding of how social dynamics affect environmental management. The findings of this study demonstrate the need to strengthen citizen participation in environmental management and propose strategies to promote sustainability in vulnerable neighborhoods. With this, it is expected to contribute to the construction of a more resilient community committed to the care of the environment.
Este análisis trata la problemática ambiental en el barrio Urseza 3- sector 4, de la parroquia Puerto Bolívar, Machala, enfocándose en la función del Trabajador Social en la administración del impacto ambiental. Se analizan las condiciones ambientales del área, las opiniones de la comunidad acerca de la polución y las tácticas puestas en marcha para atenuar sus impactos adversos. Mediante un método participativo, el estudio aspira a entender la conexión entre la administración ambiental y la comunidad, subrayando la relevancia de la educación en medio ambiente y la cooperación entre entidades sociales y gubernamentales. Para lograrlo, se utilizaron técnicas cualitativas, que incluyen entrevistas a residentes y líderes de la comunidad, observaciones directas y estudio de documentos. El estudio se basa en teorías ecológicas y modelos de intervención comunitaria, los cuales facilitan la comprensión de cómo las dinámicas sociales afectan la gestión del medio ambiente. Los hallazgos de este estudio evidencian la necesidad de fortalecer la participación ciudadana en la gestión ambiental y proponen estrategias para fomentar la sostenibilidad en barrios vulnerables. Con ello, se espera contribuir a la construcción de una comunidad más resiliente y comprometida con el cuidado del medio ambiente.
Keywords: TRABAJO SOCIAL; IMPACTO AMBIENTAL; GESTION DE RESIDUOS; INTERVENCION COMUNITARIA; SOSTENIBILIDAD